INFLUENCE OF TEACHING LEARNING MATERIALS ON READING READINESS SKILLS IN PRE-PRIMARY 2 IN PUBLIC SCHOOLS IN KAKAMEGA CENTRAL SUB-COUNTY, KENYA - Sembeya, Jacqueline; Ayaga , Geoffrey; Kikechi, Ronald Werunga (IJRDO- Journal of Educational Research, 2023)
Every child has the right toward education, according to which, fundamentally every government around the world has ratified. It is widely believed that children know how to learn, regardless of their bodily, logical, societal, expressive, grammatical, or additional characteristics. Thus, the purpose of the study was to assess the influence of teaching learning materials on reading readiness skills in preprimary 2 in public primary schools in Kakamega central sub-county, Kenya. It adopted a descriptive survey research design, with a target population of 464 people that consisted of 63 head teachers, 384 Pre-primary Teachers and 16 Members of the county education Board. The sample size of 214 persons was determined using the Krejcie and Morgan Table (1970) for determining sample sizes. The researcher collected data using questionnaires, interview guides and observation guide. The instruments were validated by the supervisors. Reliability of the instruments was determined through a pilot study where Spearman’s rank correlation coefficient (r) was analyzed for the two scores and found to be 0.78, thus, the instruments were reliable. Quantitative data was analyzed using descriptive and inferential statistics and presented in tables, while qualitative data was analyzed in themes and sub themes and presented using quotations. The study established that classroom-learning environment such as teaching learning materials, teacher - pupil ratio, physical facilities and teaching strategies have a statistically significant association with reading readiness skills in pre-primary 2. It was therefore recommended that there should be a consideration of different classroom-learning environment like teaching learning materials as they enhance reading readiness in preprimary 2 school pupils. The information provided by this study will benefit policymakers, community members and academicians.